Sex differences in stretch-induced hypertrophy, maximal strength and flexibility gains - Warneke, Konstantin; Zech, Astrid; Wagner, Carl-Maximilian; Konrad, Andreas; Nakamura, Masatoshi; Keiner, Michael; Schoenfeld, Brad J.; Behm, David George (Frontiers in Physiology, 2023)
Introduction: If the aim is to increase maximal strength (MSt) and muscle mass, resistance training (RT) is primarily used to achieve these outcomes. However, research indicates that long-duration stretching sessions of up to 2 h per day can also provide sufficient stimuli to induce muscle growth. In RT literature, sex-related differences in adaptations are widely discussed, however, there is a lack of evidence addressing the sex-related effects on MSt and muscle thickness (MTh) of longer duration stretch training. Therefore, this study aimed to investigate the effects of 6 weeks of daily (1 h) unilateral static stretch training of the plantar flexors using a calf-muscle stretching device. Methods: Fifty-five healthy (m = 28, f = 27), active participants joined the study. MSt and range of motion (ROM) were measured with extended and flexed knee joint, and MTh was investigated in the medial and lateral heads of the gastrocnemius. Results: Statistically significant increases in MSt of 6%–15% (p < .001–.049, d = 0.45–1.09), ROM of 6%–21% (p < .001–.037, d = 0.47–1.38) and MTh of 4%–14% (p < .001–.005, d = 0.46–0.72) from pre-to post-test were observed, considering both sexes and both legs. Furthermore, there was a significant higher increase in MSt, MTh and ROM in male participants. In both groups, participants showed more pronounced adaptations in MSt and ROM with an extended knee joint as well as MTh in the medial head of the gastrocnemius (p < .001–.047). Results for relative MSt increases showed a similar result (p < .001–.036, d = 0.48–1.03). Discussion: Results are in accordance with previous studies pointing out significant increases of MSt, MTh and ROM due to long duration static stretch training. Both sexes showed significant increases in listed parameters however, male participants showed superior increases.